2021
DOI: 10.1016/j.jcmgh.2021.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The Production and Function of Endogenous Interleukin-10 in Intestinal Epithelial Cells and Gut Homeostasis

Abstract: This review discusses the effect of interleukin-10 on the intestinal epithelium and the potential role of epithelialderived interleukin-10 in gut homeostasis.The healthy gut is achieved and maintained through a balanced relationship between the mucosal immune system, microbial communities resident in the lumen, and the intestinal epithelium. The intestinal epithelium plays an exceptionally important role in harmonizing the interaction between the host immunity and the luminal residents, as this selectively per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 97 publications
(191 reference statements)
4
24
0
Order By: Relevance
“…Larvae fed with TG and LG diets had signifcantly lower mRNA expression of tnf-α which is an important proinfammatory factor. Moreover, il-10 is an anti-infammatory cytokine produced mainly by macrophages and plays a role in counteracting and controlling excessive infammatory response [47][48][49]. In the present study, the mRNA expression of il-10 signifcantly increased with the larvae fed with TG and LG diets.…”
Section: Discussionsupporting
confidence: 55%
“…Larvae fed with TG and LG diets had signifcantly lower mRNA expression of tnf-α which is an important proinfammatory factor. Moreover, il-10 is an anti-infammatory cytokine produced mainly by macrophages and plays a role in counteracting and controlling excessive infammatory response [47][48][49]. In the present study, the mRNA expression of il-10 signifcantly increased with the larvae fed with TG and LG diets.…”
Section: Discussionsupporting
confidence: 55%
“…IL10 family cytokines share similar structures, common receptors, and downstream signaling [ 86 ]. Studies have shown that IL10 and IL22 play an important role in maintaining the health of the epithelial barrier of the intestine, and they are often deficient in patients with IBD [ 87 , 88 ]. There are significant differences in the expression patterns of IL10 and IL22 between patients with IBD and healthy individuals [ 89 , 90 ].…”
Section: Scfas Promote Intestinal Barrier Stability By Regulating Cyt...mentioning
confidence: 99%
“…This may be due to the relatively low bioavailability of IL10 to the intestinal mucosa [ 120 ]. To overcome this difficulty, researchers attempted to engineer IL10-producing probiotics to deliver IL10; however, this too has been unsuccessful [ 88 , 121 ]. Moreover, IL10 may promote the development of cancer to some extent.…”
Section: Immunonutrition Therapy Is a Viable Option For Ibdmentioning
confidence: 99%
“…TAMs play a pivotal role in impairing the functions of antitumor, cytotoxic CD8 + T cells, and natural killer cells by releasing the anti-inflammatory cytokine IL-10 [ 1 , 4 ]. Multiple distinct signaling pathways were found to be responsible for the transcriptional regulation of IL-10 in immune and non-immune cells [ 35 , 36 ]. The IL-10 promoter was activated by CREB through the ERK1/2 signaling pathway in native THP-1 cells [ 37 ].…”
Section: Discussionmentioning
confidence: 99%